Selection and Construction of Copyright Filtering Obligations - Li, Jiale (International Journal of Social Sciences and Public Administration, 2024)
With the continuous evolution of the Internet, we raise the question: in the era of Web3.0, the application of algorithmic recommendation technology makes personalized recommendation more common, but also raises the problem of copyright infringement, whether the popularity of algorithmic recommendation technology really needs the introduction of copyright filtering obligations in China? This paper explores this issue through literature analysis and theoretical analysis, and further examines the diversity of international attitudes towards the setting of copyright filtering obligations with comparative method analysis. It is found that although some scholars advocate the idea of introducing copyright filtering obligations, there is a divergence of views on this issue internationally. The U.S. focuses on the importance of freedom of expression and innovation, and advocates the maintenance of the "safe harbor" rule; the EU actively promotes copyright filtering obligations for ISPs through the Copyright Directive in the Digital Single Market, and the current promotion of buffering has also been shown. The push for algorithmic goodness has been a key factor in the introduction and construction of copyright filtering obligations in China. The success of this system is seen throughout the entire process of algorithmic recommendation, thus protecting intellectual property rights while ensuring the experience and creative freedom of Internet platform users. To achieve this goal, it is recommended that reasonable filtering standards be adopted, and that the accuracy and efficiency of the filtering system be ensured by regularly updating the centralized work comparison database and strengthening technical investment. In addition, a manual review mechanism should be introduced as a supplement to the algorithm to improve the system's fault tolerance and reduce the risk of erroneous filtering. In summary, China should focus on the ethical application of algorithms when constructing a copyright filtering system, in order to promote the synergistic development of the Internet industry and the copyright industry, and to create a digital environment that is conducive to both knowledge innovation and the protection of copyright rights and interests.